DIVERSION FOR CHILDREN FROM THE CRIMINAL JUSTICE SYSTEM: A COMPARATIVE STUDY OF MALAYSIA AND INDONESIA (Journal of International Studies, 2025)
Children’s rights in the criminal justice system are now legally recognised, as the Convention on the Rights of the Child (CRC) 1989 provides. Since Malaysia and Indonesia acceded to the CRC, both jurisdictions must provide legal safeguards to all children in the criminal justice system. However, whether these children are adequately protected at every stage of the criminal proceedings remains questionable. Consequently, exposure to the criminal justice system might have detrimental effects on the psychological, cognitive, and emotional development and well-being of children. To overcome these adverse effects, diversion is an alternative measure that can be implemented to protect children better. Thus, this research aims to meet the following objectives: a) to analyse the adequacy of the national laws governing diversion when dealing with children in Malaysia and Indonesia, (b) to examine the international instruments governing the implementation of diversion, and (c) to propose for the implementation of effective diversion for children in both jurisdictions. A doctrinal study was employed to achieve the objectives, and extensive doctrinal research on diversion was conducted. This research demonstrates that sound and informed laws and policies are crucial in improving the legal framework governing diversion, which can positively impact the well-being of children and facilitate their reintegration process. The results of this study are pivotal to stakeholders in both jurisdictions in ensuring children are afforded better legal protection, which aligns with national policies and the international legal framework.